"Justice" and "fairness" are not the same thing. (13th October 2014) - Goldman, Barry; Cropanzano, Russell
Summary Organizational justice researchers tend to treat as synonyms the terms "justice" and "fairness". We discuss different definitional arguments, concluding that these two concepts are distinct. Justice should be defined as adherence to rules of conduct, whereas fairness should be defined as individuals' moral evaluations of this conduct. Copyright © 2014 John Wiley & Sons, Ltd.